1997
DOI: 10.1209/epl/i1997-00418-8
|View full text |Cite
|
Sign up to set email alerts
|

Observation of squeezing using cascaded nonlinearity

Abstract: We have observed that the pump beam reflected by a triply resonant optical parametric oscillator, after a cascaded second-order nonlinear interaction in the crystal, is significantly squeezed. The maximum measured squeezing in our device is 30% (output beam squeezing inferred: 48%). The direction of the noise ellipse depends on the cavity detuning and can be adjusted from intensity squeezing to phase squeezing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
12

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 18 publications
0
25
0
12
Order By: Relevance
“…Below the oscillation threshold, they have been shown to generate squeezed vacuum states [1] and bi-partite entangled states. Above the oscillation threshold, they generate intensity correlated twin beams [2], squeezed reflected pump [3], bright bi-partite [4] or tri-partite [5] entangled states. Very impressive amounts of squeezing (11dB) have been recently observed below threshold [6].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Below the oscillation threshold, they have been shown to generate squeezed vacuum states [1] and bi-partite entangled states. Above the oscillation threshold, they generate intensity correlated twin beams [2], squeezed reflected pump [3], bright bi-partite [4] or tri-partite [5] entangled states. Very impressive amounts of squeezing (11dB) have been recently observed below threshold [6].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…These experimental systems have to include two parts for the second harmonic generation (SHG) firstly and then the parametric down-conversion, respectively. Besides, it has been experimentally demonstrated that the pump fields reflected from an optical cavity for intracavity SHG are the squeezed-state light fields because of the cascaded nonlinear interaction between subharmonic and harmonic fields inside the cavity [14] [15] . Z.Y.Ou [16] and C.Fabre et al [15] theoretically analyzed the quantum fluctuation and squeezing characteristics of the reflected subharmonic fields and calculated the spectra of squeezing.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to both intensity and phase correlations between the three modes that extend to the quantum regime, and eventually culminate in tripartite entanglement as we show below. So far, physicists' interest has been concentrated on the signal and idler quantum correlations [19] or on the pump squeezing [20]. The full three-mode system has indeed genuine quantum properties [21], which are partly lost when one traces out the pump mode, although the signal and idler modes remain of course entangled [10].…”
mentioning
confidence: 99%